Strategic change and its impact on organizational performance field study at the industrial and sanitary accessories manufacturing establishment (BCR) – Sétif - Ahtatache, Fateh; Rezig, Kamel (The International tax journal, 2025)
Modern organizations face various strategic challenges in a constantly changing business environment. These challenges necessitate continuous reevaluation of their strategies and management methods. Organizations are often compelled to adopt diverse measures to transform into flexible entities capable of delivering high-quality services at low costs. Given the inconclusive findings of previous studies regarding the relationship between strategic change and organizational performance, this study seeks to address this gap by examining the impact of strategic change on organizational performance within the National Corporation for Manufacturing Industrial and Health Accessories (B.C.R). The aim is to identify the effects of strategic change—categorized as routine, limited, radical, and organizational redirection—on organizational performance. To achieve the research objectives, a questionnaire was designed and distributed to a sample of 32 individuals representing department heads and division leaders. The response rate reached 79% of the research population. The data analysis was conducted using appropriate statistical methods, including mean, standard deviation, coefficient of variation, Spearman's rank correlation (RS), Pearson's correlation, simple regression, and the coefficient of determination (R²). The study results indicate that organizational performance improves with the increase in strategic change and that effective performance requires comprehensive and purposeful transformation.